Kualitas Hidup Penderita Hipertensi Di Puskesmas Sedayu II Bantul, Yogyakarta - Brune Indah Yulitasari; Maryadi Maryadi; Anggi Napida Anggraini (Faletehan Health Journal, 2021)
Hypertension is one of diseases considered as the main cause of death and disability. The incidence of hypertension is increasing rapidly each year. Hypertension impacts on socio-economic problems and quality of life. Quality of life is one's perception of his life including cultural aspect, the value system of the place where he is, his expectations, standards, and life goals. The aim of this study was to describe hypertensive patients’ quality of life at Sedayu II Bantul Public Health Center, Yogyakarta. This study was descriptive with a mixed-method design. The quantitative samples were 60 people and the qualitative samples were 3 people. The instruments were WHOQOL-BREFF quality of life questionnaire and an interview guide. The results showed that the quality of life of 80% hypertensive patients was generally good and 20% low. The physical domain was good (75%), physical activities were disturbed when hypertension recurred. The psychological domain was good (88.3%), they had no change in appearance and were still confident. The social domain was good (81.7%), they had good relations with family and community. The conclusion is the quality of life of hypertensive patients at Sedayu II Bantul Public Health Center is classified good.